Ceria–zirconia based catalysts for ethanol steam reforming. (1st August 2015) - Moretti, E.; Storaro, L.; Talon, A.; Chitsazan, S.; Garbarino, G.; Busca, G.; Finocchio, E.
Highlights: NiCo bimetallic particles over mixed Ce–Zr oxide are very active in catalytic ESR. Increased reducibility of the NiCo formulation leads to high ethanol conversion, H2 yield and CO2 selectivity above 530 °C. The basicity of ceria component limits ethene formation. Abstract: Mixed ceria–zirconia oxide (CZ91, Ce:Zr = 9:1) has been used to support Nickel (CZ91Ni), Cobalt (CZ91Co) and bimetallic Nickel/Cobalt active phases (CZ91NiCo) to be tested in Ethanol Steam Reforming reaction (ESR). H2 -TPR analyses and IR studies of adsorbed probe molecules suggest that ceria/zirconia actually favors the reduction of supported metal oxide phases. Moreover, characterization results point out that the co-presence of Nickel and Cobalt, as in the CZ91NiCo material, enhances the reducibility of both the metal oxide phases, in comparison with monometallic formulations, thus suggesting a synergetic effect between Cobalt and Nickel species. Correspondingly, bimetallic CZ91NiCo catalyst shows the best results in ESR in terms of ethanol conversion, hydrogen yield and selectivity to CO2 above 500 °C, which should be explained by the high reducibility of this sample. Ethene formation was not detected in significant amount during catalytic tests. Indeed, the basicity of ceria component is mainly characterizing the surface of this family of catalysts.